Recent Advances of Colossal Magnetoresistance in Versatile La-Ca-Mn-O Material-Based Films - Navjyoti Boora; Rafiq Ahmad; Shafaque Rahman; Nguyen Quoc Dung; Akil Ahmad; Mohammed B. Alshammari; Byeong-Il Lee (Magnetochemistry)
Hole-doped manganese oxides exhibit a gigantic negative magnetoresistance, referred to as colossal magnetoresistance (CMR), owing to the interplay between double-exchange (DE) ferromagnetic metal and charge-ordered antiferromagnetic insulator/semiconductor phases. Magnetoresistive manganites display a sharp resistivity drop at the metal–insulator transition temperature (TMI). CMR effects in perovskite manganites, specifically La0.67Ca0.33MnO3 (La-Ca-Mn-O or LCMO), have been extensively investigated. This review paper provides a comprehensive introduction to the crystallographic structure, as well as the electronic and magnetic properties, of LCMO films. Furthermore, we delve into a detailed discussion of the effects of epitaxial strain induced by different substrates on LCMO films. Additionally, we review the early findings and diverse applications of LCMO thin films. Finally, we outline potential challenges and prospects for achieving superior LCMO film properties.